Higher education system as the driver of innovation development of the country - Vlasov, Maxim (The journal of contemporary issues in business and government, 2021)
In modern economic conditions the study of aspects of country’s innovation development stimulation on a macroeconomic level is a top priority task for researchers all over the world. The article presents results of the research on patterns of the influence such factors as mass character, internationalization and state financing of higher education have on country’s innovation development parameters. Conducting correlation analysis allowed for obtaining academic proofs of the fact that in modern conditions above mentioned characteristics of higher education system define innovation development of the country in general. The first part of the article contains analytical review of the literature and identifies characteristics of higher education system the influence of which on country’s innovation development the authors consider as significant (mass character, internationalization, state financing). The second part describes the methodology of research and formulated working hypotheses. The third part is a presentation of obtained research results, whereas the fourth part contains conclusions. Theoretical importance of the conducted research is in defining patterns in which such higher education system characteristics as mass character, internationalization and financing model influence certain parameters of innovation development, in particular, the share of hi-tech export in the overall amount of industrial export and the share of research and development costs in GDP. Obtained results can serve as the basis for researchers willing to organize and continue studying and identifying resources for innovative development on macroeconomic level. Practical importance of the research is related to the fact that it provides opportunities for using obtained results in designing strategic development plans and programs on the level of both individual universities and regions or countries.